Cross-linked electrospun cartilage acellular matrix film as an anti-adhesive barrier - Kim, Moon Suk; Park, Joon Yeong; Park, Seung Hun; Min, Byoung Hyun (Transactions of the Annual Meeting of the Society for Biomaterials and the Annual International Biomaterials Symposium, 2019)
Statement of Purpose: The cartilage acellular matrix (CAM) has been utilized as a promising biomaterial candidate [1]. Additionally, CAM can inhibit the formation of fibrous tissue and of blood vessels between the injured tissue and the surrounding healthy tissues, indicating that CAM can act as an effective anti-adhesive barrier. CAM powder can easily form a physical film, but a CAM film easily dissolves in media. Therefore, in this work, we prepared a cross-linked CAM (Cx-CAM) film using glutaraldehyde (GA) as a cross-linking agent. Then, we investigated in vitro and in vivo suitability of the Cx-CAM film as the anti-adhesive barrier between an injured tissue and healthy tissues. Because adhesion may cause attachment between an injured tissue and healthy tissues through the formation of blood vessels and/or fibrinous adhesions within 7 days, thus in this work, the antiadhesive effect of Cx-CAM in an injured tissue examined at 7 days.
Keywords: Acellular matrices; Anti-adhesive; Cross linking agents; Electrospuns; Fibrous tissue; Glutaraldehydes; Healthy tissues; In-vitro